Research on the Impact of Internal Control Quality on High-quality Development of Enterprises—A Moderated Mediation Model - Zhao, Pan; Chen, Peizhe; Gong, Xilin (Journal of Global Economy, Business and Finance, 2025)
High-quality development of the macro-economy cannot be achieved without the support of micro-enterprises. This paper sorts out the impact mechanism of internal control quality on the high-quality development of enterprises, and conducts empirical analysis and verification using the balanced panel data of China’s Shanghai and Shenzhen A-share listed companies from 2013 to 2022 as the research sample. The results show that: internal control quality can significantly promote the high-quality development of enterprises and achieve it by promoting enterprise technological innovation; analyst attention can positively regulate the role of internal control quality in promoting the high-quality development of enterprises, and play the same role in the mediating effect. The conclusion can not only enrich the research on the relationship between internal control quality and high-quality development of enterprises, but also provide certain references for enterprises and governments to formulate corresponding strategies and policies.